An Analysis of the Stock Market Volatility Spread in Emerging Countries - Murat Akkaya (Istanbul Business Research (IBR), 2021)
This article provides results on the volatility spread for stock markets in emerging economies. Empirical studies on determining or predicting volatility in national and international financial markets provide information for investors. The aim of this study is also to analyze volatility spreads from the United States of America, France, Germany, Japan Turkey, China, India, Indonesia from emerging markets within the scope of EGARCH models, which take into account the asymmetric effects using daily stock returns for the period of January 2008 - April 2020. The a symmetric effect parameter (λ or µt-i/ht-1) appears to be negative and statistically significant at 1% for all countries, except the Shanghai Composite Stock Exchange, China. This result shows that the asymmetric effect, or the leverage effect in other words, is valid in stock markets other than China. The volatility spreads from the Dow Jones Industrial Average Index – USA to Borsa Istanbul and the Shanghai Stock Exchange – China. Also, the S & P 500 Index – USA is significant on the volatility spread of the Borsa Istanbul and Shanghai Stock Exchange. The volatility spread between Jakarta Stock Exchange - Indonesia and Borsa Istanbul is two-way and mutual.
Keywords: 650; Volatility; Contagion; Stock Market; E-Garch; Emerging Countries